Professor Schumpeter's Theory of Innovation - Sweezy, Paul M. (The Review of Economics and Statistics, 1943)
PROFESSOR Schumpeter is known primarily as a business-cycle theorist, but his fundamental interest is much broader than this reputation would suggest. A careful reading of his works clearly shows that objective is nothing less than to lay bare anatomy of economic change in a capitalist society. English and American economics, on other hand, has traditionally been content to confine its attention to what may be called normal functioning of capitalist economy. Such an approach, of course, does not exclude treatment of business cycle, but it does exclude larger problems of change and development, which are customarily regarded as lying within province of economic historian. The most important part of Professor Schumpeter's theory of economic development which falls within traditional scope of Anglo-American economics is that which is concerned with business cycles. Now I do not mean to suggest that there is any objection to regarding Professor Schumpeter as a business-cycle theorist, for he is certainly one of most distinguished contributors to this branch of economics; but circumstance should not be allowed, as it too frequently has, to obscure his no less distinguished and important achievements in clarifying processes of economic change. In this paper I shall ignore business-cycle problems and attempt to bring into sharp relief Professor Schumpeter's views on mechanism of economic change in capitalist economy. Professor Schumpeter's starting point is an economy from which change (though not growth) is assumed to be absent.' In other words, specific factor that causes change is abstracted. The resulting economic system is called because it is found to run on, year in and year out, in essentially same channels. The circular flow is in no sense conceived as an unrealistic construction; rather, it is an abstract construction which is intended to portray consequences of a limited number of very real economic forces. From this point, procedure is comprised of three steps: first, causative factor of change entrepreneur or innovator is analyzed as a pure type in abstraction from its economic environment; second, factor of change is inserted into model of circular flow; and third, interaction of innovator with forces at work in circular flow is subjected to exhaustive analysis. What emerges is a process of development which displays specific wave-like form of business cycle. This simplified version of Professor Schumpeter's method is intended to focus attention upon certain questions which are of crucial importance in any final evaluation of his theory. Has he really isolated and abstracted for analysis primum mobile of change? Is picture of circular flow fully satisfactory? Is result of joining two elements a correct representation of essentials of capitalist reality? The causative factor in according to Professor Schumpeter, is innovation, which is defined as doing things differently in realm of economic life. 2 If this were interpreted to mean no more than that the cause of change is change, it would, of course, be a mere petitio principii; but such an interpretation would be a misreading of Professor Schumpeter's meaning. Innovation is activity or function of a particular set of individuals called entrepreneurs. The entrepreneur is a sociological type that can be isolated and investigated independently of consequences which follow from actions of entrepreneur. Hence any suspicion of circular reasoning is unfounded. What are characteristics of entrepreneur? First, of course, ability to appreciate possibilities of an innovation; whether or not he is also discoverer or inventor of innovation is a matter of minor consequence. But even more 1 For distinction between change (or development) and growth, see J. A. Schumpeter, The Theory of Economic Development (Cambridge, Mass., I934), Ch. ii. 2J. A. Schumpeter, Business Cycles (New York, I939), Vol. i, p. 84.